Synthesis of copolyesters with bio-based lauric diacid: structure and physico-mechanical studies. Issue 87 (8th December 2017) - Chen, Meiling; Saada, Nesren A. H.; Liu, Fei; Na, Haining; Zhu, Jin
Abstract : Copolyesters developed from bio-based long-chain dicarboxylic acid show promising mechanical properties that are helpful for their application as biodegradable materials. Abstract : Lauric diacid (LCDA), also known as 1, 12-dodecanedioic acid, is used to develop a series of copolyesters along with 1, 4-cyclohexanedicarboxylic acid (CHDA) and 1, 4-butanediol (BDO). The resulting poly(butylene lauric dicarboxylate- co -butylene 1, 4-cyclohexanedicarboxylate) (PBLC) is proved to be a random copolyester with three triad sequences. When the LCDA content increases from 20 to 60 mol%, T m of the copolyester decreases from 133 to 57 °C. At the same time, the tensile modulus and strength decrease from 94 and 14 MPa to 40 and 5 MPa, respectively. Moreover, the elongation at break also drops from 640 to only 50%. However, further increasing the LCDA content to 80 mol%, the copolyester becomes amorphous with no T m, and its tensile modulus, strength, and the elongation at break all improve significantly to 68 and 7 MPa, and over 1400%, respectively. More importantly, for the homo-polymer poly(butylene lauric dicarboxylate) (PBL), it has a relatively high T m of 73 °C compared to that of polycaprolactone (PCL), but lower tensile modulus and strength, and significantly higher ductility, compared to those of PCL, linear low density polyethylene, and polybutylene succinate.